Science learning STEM-R approach: A study of students' reflective and critical thinking - Sarwi, Sarwi; Marwoto, Putut; Susilaningsih, Endang; Lathif, Yuniar Fahmi; Winarto, Winarto (Intelektual Pustaka Media Utama, 2024)
This study aimed to i) analyse learning problems in science at boarding schools for junior high school students and ii) determine the effectiveness of science learning in the context of Islamic teachings using the science, technology, engineering, and mathematics, -religion (STEM-R) approach to improve reflective and critical thinking skills. The research method applied in this study was a sequential exploratory mixed method. The research design consisted of five stages: i) qualitative data gathering, ii) qualitative data analysis, iii) quantitative data gathering, iv) quantitative data analysis, and v) data interpretation. The subjects of this study were 192 students from boarding schools and were divided into 6 groups. The research results obtained were the school, parents, science teachers and religion teachers’ vision and mission causing students to like or dislike science. An excellent teacher is viewed by students as someone who can make learning enjoyable, exhibit creativity in presenting educational material, possess the ability to motivate, link science and religion, engage in investigative activities, infuse humour, establish connections between science and everyday life, and communicate concepts effectively. Moreover, distinctions in reflective thinking and critical thinking abilities were observed between the experimental group and the control group. Learning that connects science and Islamic religion and examines STEM-R aspects is able to develop students' thinking skills.